Prevalência do aleitamento materno e ações de promoção, proteção e apoio à amamentação na atenção primária à saúde : estudo com equipes de saúde da família - Mota, Sérgia Cristina Haddad (2013)
Breastfeeding (AM), basic to the health, quality of life and survival of children in the first year of life, proved to be an effective and economical way for reducing morbidity and mortality. Primary Health Care (APS) is an important strategy for promotion and support of breastfeeding. The early cessation of breastfeeding (AME) continues being important public health problem. Evaluation of indicators of prevalence of breastfeeding in different locations is essential for proposing policies and implementation of promotion, protection and support of AM focused on the found situations. This study aimed to analyze the needs of actions to promote, protect and support the PM in APS, the perspective of the staff of USF, in the city of Araraquara, SP, from prevalence in children under six months in 2009, according to the AM indicators, a descriptive analytical approach defined by the World Health Organization, a quantitative and qualitative study. In the first step, quantitative, a secondary data about the prevalence of breastfeeding in children under six months old, rose, using the database Amamunic, 2009, for each USF in this city, transmitted to the researcher, via Internet, by the General Coordination Breastfeeding and Municipalities Project, Institute of Health State Health Secretariat of São Paulo-SP. The sample consisted of 1882 children less than one year old, of which 886 had six months. It was calculated with the Statistical Package for Social Sciences (SPSS), with the prevalence in each AME of each USF, by municipality. Two teams of USF with higher indicators of prevalence in AME and two groups with the smaller of these indicators were selected to participate in the second stage (qualitative). The purpose of the focus groups was to analyze the needs of actions to promote, protect and support the PM in APS, in view of USF teams. The results were validated by statistical significance, or t- from student, for comparison of frequency and the Qui-square test for comparison of frequency distribution. In the quantitative phase was identified that 30% of children were exclusively breastfed, which is a wide variation between the prevalence of AME among USF and some factors determinants of AME in the municipality. In the qualitative showed up four thematic units: the justifications for the profile of the prevalence of breastfeeding, the determinants of AM situation, the role of the ESF in promoting, protecting and supporting breastfeeding and proposals for the promotion, protection and support of AM in family health. Regarding the determinants of AM showed the relevance of municipality's child-birth institutions and some aspects as difficulties to maternal breastfeeding. The facilities and the difficulties to its practice related to process of work s development on USF were reported in the teams´ work. The following proposals were mentioned: the need for public policies to stimulate AM continuously, changes in the labor process in his USF, incorporating the family shares with women in AM. It is expected that these results may support health managers in planning and adoption of new actions of promotion, protection and support for breastfeeding in this municipality.